1981
DOI: 10.2307/3897849
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Reserve, Phenology, and Growth Cycles of Nine Colorado Range Species

Abstract: Nine Colorado range species were studied for two consecutive years to relate the carbohydrate reserve status with phenological stage of development and current annual growth, including leaf, twig, or seedstalk length, or plant height. The species were fourwing saltbush (A triplex canescens), antelope bitterbrush (Purshia tridentata), little rabbitbrush (Chrysothamnus vicidiflorus), fringed sagewort (A rtemisia frigida), scarlet globemallow (Sphaeralcea coccinea), blue grama (Bouteloua gracilis), western wheatg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 39 publications
8
44
0
2
Order By: Relevance
“…Plant production responses in our study were consistent with multiple field and laboratory studies indicating that B. gracilis is highly grazing resistant, while P. smithii can exhibit some negative responses (Menke and Trlica 1981;Polley and Detling 1988;Eneboe et al 2002;Milchunas et al 2008). Also consistent with previous field studies, we found elevated CO 2 influenced both species through water relations (reduced water stress; LeCain et al 2003), enhanced production of the C 3 grass (Read and Morgan 1996;Morgan et al 2004b), and reduced shoot [N] for the C 3 grass (Read and Morgan 1996;King et al 2004).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Plant production responses in our study were consistent with multiple field and laboratory studies indicating that B. gracilis is highly grazing resistant, while P. smithii can exhibit some negative responses (Menke and Trlica 1981;Polley and Detling 1988;Eneboe et al 2002;Milchunas et al 2008). Also consistent with previous field studies, we found elevated CO 2 influenced both species through water relations (reduced water stress; LeCain et al 2003), enhanced production of the C 3 grass (Read and Morgan 1996;Morgan et al 2004b), and reduced shoot [N] for the C 3 grass (Read and Morgan 1996;King et al 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Both species increased allocation of N and 15 N to regrowing shoots during the first 8 days after defoliation. However, the large allocation to shoot regrowth in P. smithii occurred at the expense of roots, while the smaller amount of N allocated to shoot regrowth in B. gracilis was not associated with a concomitant decline in root N. Over the course of a growing season, B. gracilis maintains more consistent levels of root and crown carbohydrate reserves compared to other co-occuring grasses and forb species, while P. smithii can show substantially depleted root and crown carbohydrate reserves during periods of aboveground growth (Menke and Trlica 1981). This pattern reflects the relatively high and consistent allocation of photosynthate to roots and crowns by B. gracilis, and the substantially higher root:shoot ratios found in shortgrass steppe dominated by B. gracilis, as compared with other grassland ecosystems .…”
Section: Grazing Tolerance and Avoidance Strategiesmentioning
confidence: 84%
See 1 more Smart Citation
“…The continued oversupply and accumulation of carbon suggest that storage carbohydrates have an important ecological role. The following hypotheses have been proposed to account for the functional significance of storage: (1) support of vegetative regrowth following dormancy (Menke and Trlica 1981), (2) support of sexual or vegetative reproduction during the absence or shortage of photosynthesis (Tissue and Nobel 1990), (3) recovery from herbivory (Dankwerts 1993) and (4) survival during dormant periods and under shading (Wyka 1999).…”
Section: Introductionmentioning
confidence: 99%
“…En effet, elle laisse sur place soit des sols fortement dénudés, soit à une nouvelle végétation indésirable, à une prolifération des espèces buissonnantes et non fourragères et à une augmentation des espèces annuelles éphémères aux dépens de la régénération naturelle (Boujghagh et Chajia, 2001). Les effets directs du broutage sur la production et la survie des ligneux ont été profondément étudiés par plusieurs chercheurs en simulant le broutage des herbivores en coupant des feuilles, rameaux et petites branches (Willard et McKell, 1978 ;Menke et Trlica, 1981 ;Tothill et Mott, 1985 ;Roy, 1991). Il ressort de ces études que l'impact d'une exploitation des ligneux dépend de la quantité d'eau et d'éléments nutritifs extraite du système, de la saison, de la fréquence de prélèvement et de la capacité de la plante à supporter le stress.…”
Section: Discussionunclassified